2017
DOI: 10.1186/s13075-016-1214-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of soluble CD163 in polymyositis-related or dermatomyositis-related interstitial lung disease

Abstract: BackgroundMacrophage activation is involved in the pathogenesis of polymyositis (PM)/dermatomyositis (DM). CD163, a scavenger receptor expressed on the surface of activated macrophages, mediates anti-inflammatory functions. This study aimed to evaluate the clinical significance of soluble CD163 (sCD163) in PM/DM-related interstitial lung disease (ILD).MethodsThe main subjects were 48 patients with PM/DM-related ILD. As controls, 10 patients with PM/DM without ILD and 20 healthy volunteers were enrolled. In pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…Enomoto et al revealed that patients with higher serum sCD163 (a marker of macrophage activation) had significantly lower survival rates that those with lower sCD163. Alveolar infiltration of CD163‐positive macrophages was evident in lungs of patients with DM‐related ILD, and was particularly more severe in the non‐survivors’ lungs . Our findings indicate not only serum neopterin as a possible prognostic biomarker for DM, but also the potential role of activated macrophages in the immunopathogenesis of DM.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Enomoto et al revealed that patients with higher serum sCD163 (a marker of macrophage activation) had significantly lower survival rates that those with lower sCD163. Alveolar infiltration of CD163‐positive macrophages was evident in lungs of patients with DM‐related ILD, and was particularly more severe in the non‐survivors’ lungs . Our findings indicate not only serum neopterin as a possible prognostic biomarker for DM, but also the potential role of activated macrophages in the immunopathogenesis of DM.…”
Section: Discussionmentioning
confidence: 63%
“…In a previous study, we found significantly increased serum levels of soluble CD163 (sCD163) in polymyositis and DM patients, and patients with high serum sCD163 levels also showed a higher incidence of CD163 + macrophage infiltration in muscle tissue [39]. The elevated serum sCD163 levels were further confirmed in two independent Japanese cohorts [40,41]. Enomoto et al revealed that patients with higher serum sCD163 (a marker of macrophage activation) had significantly lower survival rates that those with lower sCD163.…”
Section: Discussionmentioning
confidence: 75%
“…Intriguingly, imbalance in macrophage phenotype features and macrophage activation have been lately considered essential for the development of inflammatory-autoimmune, fibrotic, infective and neoplastic disorders characterized by lung involvement [ 11 16 ]. Macrophages have been initially categorized as classically (M1) or alternatively activated (M2), mirroring T cells categories.…”
Section: Introductionmentioning
confidence: 99%
“…showed that higher soluble CD163 levels were associated with worse prognosis and forced volume vital percentage of predicted value. [39] Additionally, the measurement of several serum biomarkers,…”
Section: Discussionmentioning
confidence: 99%